Pengaruh Fasilitas terhadap Keputusan Menginap pada Jasa Layanan Hotel di Palembang - Ridho, Sari Lestari Zainal; Marisa, Dwi Putri (Jurnal Kepariwisataan dan Hospitalitas; Vol 7 No 1 (2023): Vol.7,No.1,2023, 2023)
Abstra ct   This study aims to determine whether facilities affect the decision to stay at one of accommodation facilities in Palembang. This research method is a quantitative method, and the sampling method of this research is cluster sampling, namely customers staying at t he h otel with a total of 90 respondents. Data collection was carried out by questionnaire survey methods and literature studies. The test of data analysis of the instrument used is a test of validity and reliability. The classical assumption test uses the normality test and the hypothesis test using simple linear regression analysis methods, the coefficient of determination, and the t test. The results of the study through simple regression analysis are Y = 14.485 + 0.571X. The constant is 14.485, meaning that if the facility variable has a fixed or constant value, then the overnight decision is 14.485. This means that it is not affected by the facility variable, then the stay decision will still be valued at 14,485. The regression coefficient of 0.571 means that if the facility variable increases, the Stay Decision will increase by 0.571 units assuming the other variables remain constant. The results of the R2 value analysis of this study are known to be 0.326. So that the influence of facilities on the decision to stay at the h otel is 32.6%, while the remaining 67.4% is influenced by other factors. So it can be concluded that facilities influence the decision to stay. The resulting t-test value is 6.517, while the ttable is 1.662. Therefore H0 is rejected, which means that there is an overall influence of the facility on the decision to stay.